PALEOGEOGRAPHY OF THE WEST SIBERIAN PLAIN DURING THE SARTAN GLACIATION (IN RELATION TO FINDINGS OF MAMMOTHS AND PALEOLITHIC SITES) - Kuz'min Ya.V.; Zol'nikov I.D.; Orlova L.A.; Zenin V.N. (My University, 2004)
Recently obtained great body of new data makes it possible to affirm that the abundance of glaciers in the northern part of West Siberia and the formation of giant impounded lakes as a result of the damming of the Ob and Yenisei rivers took place in the preceding glacial epoch (about 90000-60000 yr BP, i.e., during the Ermakovo Glaciation) rather than the Sartan time. As to Sartan glacial lakes, they had smaller dimensions, because of the predominantly mountain-and-valley nature of the last glaciation in northern Siberia. Thus, the paleogeographic environment of even the Sartan Glacial Maximum in West Siberia was subaerial, with ephemeral shallow lakes. The periglacial-type landscapes of that time supported the existence of large herbivores (mammoth, woolly rhinoceros, bison, horse, and other species).